Patterns of human growth - Bogin, Barry, 1950- (Cambridge studies in biological and evolutionary anthropology ;, 2021)
This completely revised edition provides a synthesis of the forces that shaped the evolution of the human growth pattern, the biocultural factors that direct its expression, the intrinsic and extrinsic factors that regulate individual development, and the biomathematical approaches needed to analyze and interpret human growth. After covering the history, philosophy and biological principles of human development, the book turns to the evolution of the human life cycle. Later chapters explore the physiological, environmental and cultural reasons for population variation in growth, and the genetic and endocrine factors that regulate individual development. Using numerous historical and cultural examples, social-economic-political-economic forces are also discussed. A new chapter introduces controversial concepts of community effects and strategic growth adjustments, and the author then integrates all this information into a truly interactive biocultural model of human development. This remains the primary text for students of human growth in anthropology, psychology, public health and education.